Isolation and genotyping of sorbitol fermenting of E.coli O157:H- strain isolated from children and calves in AL –Samawa Province - Jarad, Ahmed Sami; R. M. Al-Samawy, Eyhab (Al-Qadisiyah Journal of Pure Science, 2018)
Infections with Shiga toxin Escherichia coli (STEC) are the important cause of several sever disease in human and animal. Non-sorbitol-fermenting O157:H7 is fundamental and most regular isolated. However, sorbitol-fermenting (SF) O157: H- strains are significantly increased and cannot detected by routine lab test. Current study designed to isolate and genotyping of SF-O157: H- in samples collected from 125 children manifested with diarrhea in Pediatric Hospital and 135 calves with or without diarrhea from local farm in Al –Samawa Province. Isolation and diagnostic procedure depends on selective culturing media to then all samples cultured on CHROMagar O157 to detect E. coli O157 from other intestinal flora. Then, the isolated (O157) was streaking onto Sorbitol MacConkey agar and store in incubator at 37 °C for 24h and examined for typical E. coli O157:H7, then the isolated SF- O157: H- were subjected to various biochemical tests include IMViC (Indole, Methyl red, VogesProskauer, and Citrate) to affirm proof of E.coli. And latex agglutination checking to serotyping of E.coli O157: H7 was done. .All isolated SF-O157: H- were tested for the carrying of flowing genes rfbEO157, FlicH7, stx1, stx2, EHEC hlyA, eaeA by PCR assey. Results showed the ratio of SF- O157: H- were 8 of out 125 at a percentage (6.4 %) in sample collected from children and 16 / 135 at a percentage (11.8 %) in calves and Prevalence of virulent genes (rfbO157, flicH7, stx1, stx2, eaeA, and EHEC hlyA) among SF- O157 were, rfbO157 gene of SF- O157:H- gave 87.5% (7/8) and 100%(16/16) in children and calves respectively, flicH7 gave negative result in all isolated, and 37.5 % (3/8) expressed stx1 gene in children and 31.2 % (5/16) in calves, the stx2 gene appeared in 12.5 %(1/8) and 6.25 %(1/16) in children and calves respectively, eaeA gene gave a positive results were 50%(4/8) in children and 43.7 %(7/16) in calves and EHEC hlyA gene results were 25%(2/8) and 6.25 %(1/16) from both children and calves respectively. SF- O157: H- strains have variant number of virulent factor, some strain has one or two, three and may have all virulence or no virulent detected with them in some case. In conclusion, SF- O157: H- is important pathogen to human especially children, and cow are the fundamental store to this pathogen particularly calves and can infect it, SF- O157: H- carry important virulence factors (stx1, stx2, eaeA and EHEC HlyA) and cannot detected by routine lab test as SMAC, so the best detected method by using PCR assay for the main virulent factor.